Patient-Reported Outcomes Measurement Information System (PROMIS) instruments among individuals with symptomatic knee osteoarthritis: a cross-sectional study of floor/ceiling effects and construct validity. - Driban, Jeffrey B.; Morgan, Nani.; Price, Lori Lyn.; Cook, Karon F.; Wang, Chenchen. (2016)
Background: The psychometric properties of Patient Reported Outcomes Measurement Information System (PROMIS) instruments have been explored in a number of general and clinical samples. No study, however, has evaluated the psychometric function of these measures in individuals with symptomatic knee osteoarthritis (KOA). The aim of this project was to evaluate the construct (structural) validity and floor/ceiling effects of four PROMIS measures in this population.; Keywords: Patient Reported Outcomes Measurement Information System, Western Ontario and McMaster Universities Arthritis Index, Short form-36, Beck Depression Inventory Second Edition, Physical Component Summary, Mental Component Summary.; Springer Open.